New mixed-ligand Zn(ii)-based MOF as a nanocarrier platform for improved antibacterial activity of clinically approved drug levofloxacin. (29th March 2023) - Bhat, Zia Ul Haq; Hanif, Summaiya; Rafi, Zeeshan; Alam, Mohammad Jane; Ahmad, Musheer; Shakir, M.
Abstract : The advancement of metal–organic frameworks (MOFs) operating as drug delivery systems is of extensive interest as their controlled drug release and specific delivery are very propitious. Abstract : The advancement of metal–organic frameworks (MOFs) operating as drug delivery systems is of extensive interest as their controlled drug release and specific delivery are very propitious. Herein, we report a new metal–organic framework (Zn-nMOF) formulated from a mixed ligand system comprising 5-hydroxyisophthalate ions (L1 ) and 5, 5′-dimethyl-2, 2′-bipyridine (L2 ) with zinc ions serving as metal centers. The crystal structure of the synthesized MOF was determined by single-crystal X-ray analysis and further supported by FTIR, PXRD, TEM, SEM, EDX, and UV/visible spectroscopy. The loading of a clinically approved broad-spectrum drug levofloxacin onto this zinc-based MOF was achieved by activating the pendent hydroxyl groups of the organic linker (5-hydroxyisophthalic acid) onto the surface of the MOF using the activator 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide (EDC). The confirmation of successful conjugation of levofloxacin onto the MOF and formation of Levo@Zn-nMOF was well supported by FTIR, UV/visible, SEM, and EDX techniques. The levofloxacin-conjugated Zn-nMOF (Levo@Zn-nMOF) showed increased antibacterial efficacy compared to pure levofloxacin against Gram-positive and Gram-negative bacteria, specifically S. aureus (MIC-64.4 μg mL −1 ), B. subtilis (MIC-94.97 μg mL −1 ), E. coli (MIC-26.0 μg mL −1 ), and P. aeruginosa (MIC-67.48 μg mL −1 ). The efficiency of conjugated levofloxacin showed improvement by 1.65 times, 1.71 times, 1.56 times, and 1.03 times in S. aureus, B. subtilis, E. coli, and P. aeruginosa, respectively. This work shows that a significant increase in antibacterial efficacy can be achieved for certain antibiotics by conjugating them to the MOF surface through a covalent bond linkage.